Deployment Strategies of EV School Buses with Vehicle to Grid (V2G) in the US School System - Pallav Prakash (International Journal of Supply Chain Management, 2023)
Governments across the world are pushing for speedier adoption of electric vehicles (EVs) in order to meet their target for transition to a greener and cleaner environment that has low or zero carbon emission. Transportation being one of the major contributors to environmental pollution because of incessant burning of fossil fuels. EVs are being considered to be the best possible solution to alleviate vehicular pollution. However, proliferation of EVs create additional burden on the power grids. The consumption of electrical power is steadily rising because of even-growing population and the demand is particularly higher during summer months due to higher use of air conditioners. To ease this pressure on the grid the novel vehicle-to-grid or V2G technology is being employed whereby idle electric vehicles can be put to use as giant batteries that can send power back to the grid to supplement its output. With the wide scale adoption of electrical buses is schools this turns out to be a feasible option. Battery driven school buses are best suited for this. These vehicles remain idle for major portion of the day and also during summer months and can be effectively utilized for generating electricity using their batteries. However, there are challenges involved in the implementation of this strategy. Besides lack of charging infrastructure and limited knowledge of owners about the nature and benefits of the implementation there are also problems of rapid battery degradation, lack of control on the vehicle and the process and high costs involved. Nevertheless, using literature review this article explains the rationale behind adoption of the technology and highlights, the strategies that can be adopted to effectively exploit this novel technology to make the most out of idle electric school buses to support public utilities. To an extent electric school buses and the v2g technology can be potentially helpful for stabilizing supply of electricity during peak hours and improve efficiency of supply chain management of several industries including the power sector.